Shock impedance amplified impact deformation of zircon in granitic rocks from the Chicxulub impact crater - Wittmann, A.; Cavosie, Aaron; Timms, Nick; Ferrière, L.; Rae, A.; Rasmussen, C.; Ross, C.; Stockli, D.; Schmieder, M.; Kring, D.A.; Zhao, J.; Xiao, L.; et al. (ELSEVIER, 2021)
Zircon is a precise chronometer and prominent recorder of impact deformation. However, many impact-induced features in zircon are poorly calibrated, sometimes due to contradicting experimental data, in other instances due to the lack of systematic studies of impact-deformed zircon. To resolve issues with the shock petrographic use of zircon, we classified impact deformation features in 429 zircon grains in a continuous drill core of uplifted, granitic bedrock in the peak ring of the 200-km-diameter K-Pg Chicxulub impact structure. Following initial identification in backscattered electron (BSE) images, Raman spectroscopy and electron backscatter diffraction confirmed one reidite-bearing zircon grain. Quartz-based shock barometry indicates the host rock of this zircon-reidite grain experienced an average shock pressure of 17.5 GPa. A survey of BSE images of 429 ZrSiO4 grains found brittle deformation features are ubiquitous, with planar fractures in one to five sets occurring in 23% of all zircon grains. Our survey also reveals a statistically significant correlation of the occurrence of planar fractures in zircon with the types of host materials. Compared to zircon enclosed in mafic, higher density mineral hosts, felsic, low-density minerals show a much higher incidence of zircon with planar fractures. This finding suggests amplification of pressure due to shock impedance contrasts between zircon and its mineral hosts. Using the impedance matching method, we modeled the shock impedance pressure amplification effect for zircon inclusions in Chicxulub granitic hosts. Our modeling indicates shock impedance could have amplified the average 17.5 GPa shock pressure in a zircon inclusion in quartz or feldspar in the Chicxulub granitic rocks to 24 ± 1 GPa, suggesting that reidite in these rocks formed between 17.5 and 25 GPa. In essence, our study of impedance-induced shock pressure amplification in zircon assemblages, including the onset of reidite formation, details how shock impedance in mineral associations can be quantified to refine shock pressure estimates.